If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 3n = 8 + 2n Solving 1 + 3n = 8 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 1 + 3n + -2n = 8 + 2n + -2n Combine like terms: 3n + -2n = 1n 1 + 1n = 8 + 2n + -2n Combine like terms: 2n + -2n = 0 1 + 1n = 8 + 0 1 + 1n = 8 Add '-1' to each side of the equation. 1 + -1 + 1n = 8 + -1 Combine like terms: 1 + -1 = 0 0 + 1n = 8 + -1 1n = 8 + -1 Combine like terms: 8 + -1 = 7 1n = 7 Divide each side by '1'. n = 7 Simplifying n = 7
| 12x3/9y8= | | x=81/9(10-1) | | 7.0-3x=1 | | X*2+1=3x+11 | | 5(3x+6)+4=15x+34 | | 2/7x=56 | | 20a*48a= | | 4y+7=4y-6 | | c+19.1=12.1 | | 3(n+1)=6n-9 | | X+3=-2x+12 | | 20a+48a= | | L+21=(-l)+87 | | v/4--10=13 | | |cos(x-pi/4)|=rad2/2 | | 5m-4+3m=24 | | z/3=1.49 | | 8x=17x-3 | | 7w+4-2=6w+4 | | 13=2j+5 | | -3p+9=-6 | | -8m+4=-44 | | 2+-3g=5 | | y/6-6=6 | | 23x=24x-5 | | 4m-2=5m+4-m | | 42-8m=57 | | 7x+11+23=53 | | 7x+11+34=53 | | 32x-10=40x-14 | | y=4y-48 | | 13-6v-4=-6v-9 |